OPTIMALISASI PERAN SATUAN LALU LINTAS DALAM MENCEGAH KECELAKAAN LALU LINTAS DAN IMPLIKASINYA TERHADAP KETAHANAN WILAYAH (Studi Di Satuan Lalu Lintas Wilayah Jakarta Timur, DKI Jakarta - R Sinaga (Universitas Gadjah Mada, 2014)
This paper explained the police role optimization to prevented traffic accident. The purpose of this paper was discovering the police enforcement role in preventing traffic accident and the implication of traffic police optimization on regional resilience in Jakarta Timur DKI Jakarta area. The study was conducted first at the accident critical points and directly visited the Jakarta Timur certain points. Second was, driver and vehicle registration/ identification. Third was Police Traffic Law Enforcement, it is a preventive and repressive effort. Fourth was operational management and Police Traffic Engineering, Fifth was Police Traffic Education. The education was provided for the driver of two and four wheels vehicle. The driver education was intensified by the Jaktim area Traffic Unit at certain points. The obstacles of the Jakarta Timur area’s Traffic Unit duty were the lack of human resources, facilities and infrastructure, and the minimum community’s support. The implication of Jakarta Timur area Traffic Unit optimization in preventing traffic accident on regional resilience was able to be concluded.Keywords: Role, Traffic Unit, Accident, Regional Resilience.